Qualidade de mudas seminais de eucalipto em função dos substratos e fertilização de liberação controlada - Da Silva, Richardson Barbosa Gomes [UNESP]; Simões, Danilo [UNESP]; Andrade, Fernando Reis [UNESP]; Da Silva, Magali Ribeiro [UNESP] (My University, 2013)
For the production of quality seedlings, depending on the physical characteristics of each substrate, more rational nutritional managements, from the of economic-environmental point of view, should be sought. This study aimed to evaluate the development and quality of Eucalyptus grandis × E. urophylla seedlings in terms of substrates and doses of controlledrelease Osmocote® fertilizer. The experiment was conducted with a completely randomized, factorial design, using as substrates: vermiculite+carbonized rice chaff+coconut fiber (1:1:1); vermiculite+coconut fiber (1:1) and vermiculite+coconut fiber (2:1) and doses of 2, 4, 6 and 8kg·m -3 of substrate. The substrates with higher water holding capacity allow seedlings to reach their maximum development in most parameters using lower doses of controlled-release fertilizer. We recommend the application of the controlled-release fertilizer at a dose of 6.0kg·m-3 in vermiculite+carbonized rice chaff+coconut fiber (1:1:1) and vermiculite+coconut fiber (2:1) substrates, and in substrate vermiculite+coconut fiber (1:1) at a dose of 7.0kg·m-3. In each substrate there is a dose range that promotes a greater formation of suitable root systems for planting in the field, which consequently results in seedlings with greater morphological development at nursery.
Quality of eucalyptus seedlings as a function of substrates and controlled-release fertilization